MOLECULAR MECHANISMS OF ANTINEOPLASTIC ACTION OF AN ANTICANCER DRUG ELLIPTICINE - Stiborova, Marie; Rupertova, Martina; Schmeiser, Heinz H.; Frei, Eva (Biomedical papers, 2006)
Ellipticine is a potent antineoplastic agent exhibiting the multimodal mechanism of its action. This article reviews the mechanisms of predominant pharmacological and cytotoxic effects of ellipticine and shows the results of our laboratories indicating a novel mechanism of its action. The prevalent mechanisms of ellipticine antitumor, mutagenic and cytotoxic activities were suggested to be intercalation into DNA and inhibition of DNA topoisomerase II activity. We demonstrated a new mode of ellipticine action, formation of covalent DNA adducts mediated by its oxidation with cytochromes P450 (CYP) and peroxidases. The article reports the molecular mechanism of ellipticine oxidation by CYPs and identifies human and rat CYPs responsible for ellipticine metabolic activation and detoxication. It also presents a role of peroxidases (i.e. myeloperoxidase, cyclooxygenases, lactoperoxidase) in ellipticine oxidation leading to ellipticine-DNA adducts. The 9-hydroxy- and 7-hydroxyellipticine metabolites formed by CYPs and the major product of ellipticine oxidation by peroxidases, the dimer, in which the two ellipticine skeletons are connected via N6 of the pyrrole ring of one ellipticine molecule and C9 in the second one, are the detoxication metabolites. On the contrary, 13-hydroxy- and 12-hydroxyellipticine, produced by ellipticine oxidation with CYPs, the latter one formed also spontaneously from another CYP- and peroxidase-mediated metabolite, ellipticine N2-oxide, are metabolites responsible for formation of two ellipticine-derived deoxyguanosine adducts in DNA. The results reviewed here allow us to propose species, two carbenium ions, ellipticine-13-ylium and ellipticine-12-ylium, as reactive species generating two major DNA adducts seen in vivo in rats treated with ellipticine. The study forms the basis to further predict the susceptibility of human cancers to ellipticine.
Keywords: Ellipticine/Anticancer drug/Cytochrome P450/Peroxidase/Mechanism of action/DNA adducts